MR elastography of prostate cancer: quantitative comparison with histopathology and repeatability of methods - Sahebjavaher, Ramin S.; Nir, Guy; Honarvar, Mohammad; Gagnon, Louis O.; Ischia, Joseph; Jones, Edward C.; Chang, Silvia D.; Fazli, Ladan; Goldenberg, S. Larry; Rohling, Robert; Kozlowski, Piotr; Sinkus, Ralph; et al. (NMR in biomedicine, 2015)
The purpose of this work was to assess trans‐perineal prostate magnetic resonance elastography (MRE) for (1) repeatability in phantoms/volunteers and (2) diagnostic power as correlated with histopathology in prostate cancer patients. The three‐dimensional (3D) displacement field was obtained using a fractionally encoded gradient echo sequence using a custom‐made transducer. The repeatability of the method was assessed based on three repeat studies and by changing the driving frequency by 3% in studies on a phantom and six healthy volunteers. Subsequently, 11 patients were examined with MRE prior to radical prostatectomy. The areas under the receiver operating characteristic curves were calculated using a windowed voxel‐to‐voxel approach by comparing the 2D registered slides, masked with the Gleason score. For the repeatability study, the average intraclass correlation coefficient for elasticity images was 99% for repeat phantom studies, 98% for ±6 Hz phantom studies, 95% for volunteer repeat studies with 2 min acquisition time, 82% for ±2 Hz volunteer studies with 2 min acquisition time and 73% for repeat volunteer studies with 8 min acquisition time. For the patient study, the average elasticity was 8.2 ± 1.7 kPa in the prostate capsule, 7.5 ± 1.9 kPa in the peripheral zone (PZ), 9.7 ± 3.0 kPa in the central gland (CG) and 9.0 ± 3.4 kPa in the transition zone. In the patient study, cancerous tissue with Gleason score at least 3 + 3 was significantly (p < 0.05) different from normal tissue in 10 out of 11 cases with tumors in the PZ, and 6 out of 9 cases with tumors in the CG. However, the overall case‐averaged area under the curve was 0.72 in the PZ and 0.67 in the CG. Cancerous tissue was not always stiffer than normal tissue. The inversion algorithm was sensitive to (i) vibration amplitude and displacement nodes and (ii) misalignment of the 3D wave field due to subject movement. Copyright © 2014 John Wiley & Sons, Ltd. This study presents the first MR elastography study of prostate cancer that compares imaging with full‐mount histopathology (Gleason score). Though the overall AUC was poor due to many false positives, a significant difference (p < 0.05) between normal and cancerous tissue was identified in most cases. The repeatability of the method was tested in phantoms and volunteers, and it was observed that the inversion algorithm was sensitive to (i) vibration amplitude and displacement nodes, which shifted with small changes in excitation frequency, and (ii) misalignment of the 3D wave field due to slight subject movement.